Availability of Urban Infrastructure in Efforts to Establish Semarang Smart City in 2017 - Irma Fajariyah; Ariyani Indrayati; Nur ‘Izzatul Hikmah (P4W LPPM IPB, 2018)
Semarang city government has made efforts to digitize public services and provide Information and Communication Technology (ICT) infrastructure to establish Semarang as a smart city, but there are remaining problems. The objectives of this research are (1) to identify the availability of smart city infrastructure in Semarang; (2) to understand human resources that support the operation and utilization of infrastructure; (3) to provide direction for improvement and development of smart city infrastructure based on spatial approach. The variable of the research is the availability of urban ICT infrastructure, which consists of sub-variables of each infrastructure types. Analysis used in this research is secondary data analysis, together with district unit analysis using Guttman scale analysis, Scalogram analysis, and Centrality Index analysis. The result stated that there are no centrality of smart city infrastructure because the IS value is discovered 35.14 (medium), which is divided into 4 hierarchies of area services. The completeness level of facilities in each district ranged between medium (50-70%) and high (>75%). Therefore, the development of smart city infrastructure needs to be directed to southern and western regions that are in hierarchy service III and IV, balanced with the synergy between government and society in its implementation.